Recensiones - Valero Iglesias, Luis F.; I. M. B.; X. X.; S. M. A.; Mantilla Aguirre, Sebastián (ECA: Estudios Centroamericanos, 1973)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 28, No. 291-292, 1973: 81-110.